Pelatihan Mental Berwirausaha dan Perencanaan Pemasaran Wirausaha Baru Binaan Kadin Kota Bandung - Rachmawati, Rr.; Maulani, Terra Saptina (Jurnal Pengabdian Tri Bhakti, 2020)
Bandung is one of the creative city in Indonesia because has potential economic by the micro, small, and medium business sector which is engaged in the creative business. One of the government programs in an effort to foster economic activity is Program Kewirausahaan Baru (WUB). the entrepreneurs who joint in the program have a business duration of 0- 5 years. They are provided with training Dinas KUMKM Kota Bandung, and the implementation is fostered by KADIN Kota Bandung. Even though they have been given training by the WUB program, currently they are faced with a challenge where the motivation level has decreased. So, it is necessary to increase motivation and entrepreneurial mentality by training. Business competition cannot be avoided, so it's necessary to maintain business so as not to be less competitive through strategic marketing plans. The training methods used are teaching, teach to learn and practice. The output of community service activity is business motivation and marketing skills increasingly.